Post Editing: Suggestions for Translation Courses Sub-Content - Alvin Taufik (Universitas Bunda Mulia, 2019)
The practice of post-editing has become so common these days with to the introduction of Machine Translation (MT). Because of that, the author believes post-editing should be included in all types of translation activities. Subsequently, in the teaching of translation, post editing should be considered as one of the course to be taught. In translation teaching, however, especially in Indonesia, post-editing has not yet been discussed specifically. Most post-editing activities in the classroom in Indonesia is not taught specifically as one of the courses as a part of a minor. Rather, they are integrated as a sub-course of a particular course, such as literary translation. In this research, I would like to propose several inputs which can be considered when teaching post- editing as a part of a bigger course. This research is conducted by reflecting on the actual process of post-editing conducted by the researcher when translating a text. It is expected that the result of the research is to be used by translation trainers, teachers, and practitioners in training their students.Keywords: Post-editing, translation course, sub-course